Investigation of the spatio-temporal heterogeneity and optical property of water-soluble organic carbon in atmospheric aerosol and snow over the Yulong Snow Mountain, southeastern Tibetan Plateau. (November 2020) - Niu, Hewen; Kang, Shichang; Gao, Wanni; Sarangi, Chandan; Tripathee, Lekhendra; Rupakheti, Dipesh; Zhang, Guotao; Yan, Xingguo
Highlights: This is the first study on WSOC in multiple samples in a glacierized region. Light-absorbing properties of WSOC have been thoroughly investigated. There exists spatio-temporal heterogeneity of WSOC over the Mt. Yulong. Inorganic ions were the most abundant species in snow and river water samples. The transfer process of WSOC in the summer precipitation-atmosphere-snow-river water continuum has been examined. Abstract: Atmospheric aerosols are a branch of active research in recent decades. The deposition of light-absorbing substances on high-altitude glaciers causes substantial adverse impacts on the cryospheric environment, cryosphere-hydrology, and climate system. Although, the concentrations of water-soluble organic carbon (WSOC) in snow/ice on glaciers of Tibetan Plateau (TP) have been reported, their transfer processes and optical properties in the context of summer precipitation-atmosphere-snow-river water continuum are seldom studied. In this study, we have systematically examined some scientific issues associated with WSOC concentrations and light absorption properties of WSOC in various forms of samples from the Mt. Yulong region. Statistical results demonstrate that the spatial distribution of WSOC in the snow of Baishui glacier was heterogeneous. The average WSOC concentrations of each snowpit were significantly decreased, and its light-absorbing properties were significantly elevated with the time extension. Aerosol WSOC concentrations and light absorption have distinct spatial disparity and seasonal variation. Pre-monsoon and monsoon have the highest and lowest WSOC content, respectively. Whereas the light-absorbing properties present contrasting seasonal trends. Rivers of which runoff was supplied by glacier meltwater have significantly lower WSOC concentrations (e.g., 0.42 ± 0.03 mg L −1 ) compared with other forms of water bodies. Mass absorption cross-section of WSOC (MAC-WSOC ) in multiple snow and meltwater samples was significantly different and type-dependent. Atmospheric aerosol has the lowest MAC-WSOC value among the four types of samples, which was likely associated with exhaust emissions from private vehicles and tour buses. Statistical results indicated that the average AAE330-400 values of various snow/ice samples are subequal. Snow of glaciers supplies a desirable platform for the deposition of gaseous materials which experienced long-range transport in high altitude zones. Biomass-burning emissions made an immense contribution to the WSOC deposition over the study area, as demonstrated by the distribution of active fire points. However, this preliminary study represents the first systematic investigation of WSOC deposition in southeastern TP. Further robust in-situ field investigations and laboratory measurements are urgently necessary to improve our understanding of the transfer process and optical property of WSOC.